Peran Manajemen Sekolah dalam Meningkatkan Prestasi Sekolah (Studi kasus pada SD Pertiwi Abhilasa) - Ni Luh Man Eristia; I Made Awanita; I Ketut Lila Murti (Jurnal PASUPATI, 2020)
The progress of the school is very dependent on the role of the principal in leading the school, in addition there is the role of a teacher in assisting the headmaster in advancing the quality of education in schools and other collaborative school residents to help develop academic quality and improve the quality of the school so that it still exists and is able to compete with the school Another and the most important thing is to collaborate with students 'parents to develop their students' potential.From this background the authors are interested in conducting research by taking the title of the thesis "The Role of Good School Management can improve School Achievement (Case Study at Pertiwi Abhilasa Elementary School)".This study aims to determine the implementation of school management and to determine the implications of the implementation of the quality learning in SD Pertiwi Abhilasa. This type of research is qualitative research. This research is descriptive qualitative, the data collected in the form of words from the results of in-depth interviews and in the form of pictures. So that using primary data and secondary data complement each other.This research is showing there are relation role of school management in Pertiwi Abhilasa Elementary School so as to improve school performance in accordance with G.R Terry's theory in school management it requires planning, organizing, implementing, monitoring, evaluating and following up. However, for school facilities and infrastructure facilities are still minimal, and the marketing management of Pertiwi Abhilasa Elementary School still needs to be developed to highest level as possible so number of students can be increases every year. Keywords: Role, Management, School, Achievement